Theoretical aspects of heterosis - L. V. Khotyleva; A. V. Kilchevsky; M. N. Shapturenko (Вавиловский журнал генетики и селекции, 2016)
The phenomenon of heterosis, known as superior performance of hybrid organism compared with either of their parents, has been exploited by agricultural practices in the production of various crops since the beginning of the last century; however, its genetic basis has remained obscure. With experimental data obtained from the study of maize hybrids, and mathematical calculations, some genetic models have been proposed to explain heterosis from various types of gene interaction, such as dominance, over-dominance and epistasis. However, any of the proposed concepts has weak points, which place limitations on the possibility of overall interpretation of heterotic response in F1. In this review we gather a brief account of findings from various studies for critical evaluation of the main theoretical concepts based on the information accumulated to date by genetics and molecular biology and focused on particular mechanisms acting for specific traits. We discussed some aspects concerning the role of mutation loads in the formation of heterotic phenotype. Also, we gathered a brief account of findings for interpretation of genetic effects due to linkage and non-allelic genes’ interactions that make nuances to analysis of dominance and over-dominance. We have provided information about combining ability, its practical application in the context of the concept of heterotic groups. Here we also discussed some aspects of “genotype–environment” interaction. Recent advancements in genetics and molecular biology indicate the importance of various types of gene action for heterosis and confirm the necessity of systemlevel approaches to understanding this unique phenomenon.